An Analysis of Contributions and Effectiveness of Government Regulation No. 23 Year 2018 in Tax Revenue: a Case Study at KPP Pratama Pekalongan - Puspita Dewi W; Atiqoh Fitri Lailani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
This study aims to determine the levels of contributions and effectiveness of Government Regulation No. 23 Year 2018 (PP No. 23/2018) on tax revenue at KPP Pratama Pekalongan. It used effectiveness and contributions formulas for data analysis. The research results showed that the effectiveness level of this regulation on tax revenue at KPP Pratama Pekalongan indicating ineffective criterion. On the one hand, the contribution level of this regulation implementation on tax revenue at KPP Pratama Pekalongan indicating very poor criterion. Based on the data collected, this regulation were unable to increase the tax revenue at KPP Pratama Pekalongan.